Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1021/acs.analchem.3c01857
|View full text |Cite
|
Sign up to set email alerts
|

Natural Microbial Reactor-Based Sensing Platform for Highly Sensitive Detection of Inorganic Arsenic in Rice Grains

Abstract: Rice is a major dietary source of inorganic arsenic (iAs), a highly toxic arsenical that accumulates in rice and poses health risks to rice-based populations. However, the availability of detection methods for iAs in rice grains is limited. In this study, we developed a novel approach utilizing a natural bacterial biosensor, Escherichia coli AW3110 (pBB-ArarsR-mCherry), in conjunction with amylase hydrolysis for efficient extraction, enabling high-throughput and quantitative detection of iAs in rice grains. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Compared with the high temperature and strong acid environment of microwave digestion, enzymatic hydrolysis possesses obvious advantages in maintaining the stability of As species, making it more suitable for biosensing analysis. Our previous work has also demonstrated that the enzymatic hydrolysis method can better prevent As­(III) oxidation under relative mild conditions . Comparing with the commonly used microwave digestion method, the arsenic concentrations obtained by the two methods did not deviate significantly.…”
Section: Resultsmentioning
confidence: 83%
See 3 more Smart Citations
“…Compared with the high temperature and strong acid environment of microwave digestion, enzymatic hydrolysis possesses obvious advantages in maintaining the stability of As species, making it more suitable for biosensing analysis. Our previous work has also demonstrated that the enzymatic hydrolysis method can better prevent As­(III) oxidation under relative mild conditions . Comparing with the commonly used microwave digestion method, the arsenic concentrations obtained by the two methods did not deviate significantly.…”
Section: Resultsmentioning
confidence: 83%
“…Our previous work has also demonstrated that the enzymatic hydrolysis method can better prevent As(III) oxidation under relative mild conditions. 33 Comparing with the commonly used microwave digestion method, the arsenic concentrations obtained by the two methods did not deviate significantly. We investigated samples of rice from different regions in China, including Dongbei, Guangxi, Hubei, Hunan, and Jiangsu.…”
Section: Ecl Analysis Of As(iii)mentioning
confidence: 87%
See 2 more Smart Citations
“…A natural bacterial biosensor utilising Escherichia coli AW3110 (pBB- Arars R- m Cherry), in conjunction with amylase hydrolysis for extraction has been used for the quantitative detection of iAs in rice grains. 58 The biosensor exhibited high specificity for As and it was possible to distinguished between As III and As V by modulating the concentration of PO 4 3− in the detection system. The iAs concentrations were determined in 19 rice grain samples with varying total As concentrations and compared with a reference technique using enzymatic hydrolysis and microwave digestion coupled with HPLC-ICP-MS.…”
Section: Elemental Speciation Analysismentioning
confidence: 99%